Analisis Gaya Belajar VAK (Visual, Auditorial, Kinestetik) Siswa di MTsN 4 Pasaman Barat - Fitri Aswanto; Fadhilla Yusri; Haji Kurniawan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research began with many teachers not understanding the learning styles or ways of learning that children have so that many of the lessons delivered by teachers were not understood during the learning process. So, it is important for teachers to master the three learning styles, namely visual, auditory and kinesthetic, to make it easier for students to understand what is conveyed by the teacher in the teaching and learning process and a teacher can also improve the quality of their learning. The subjects of this research were all students from class 7.1 to class 7.7, the total number of which was 223. The results obtained in the research were that the learning style of class 7.1 students was dominated by the Kinesthetic learning style as much as (43%) of the total students in class 7.1, class 7.2 was dominated by the Auditorial learning style. as much as (50%), class 7.3 is dominated by an Auditory learning style as much as (35%), class 7.4 is dominated by a Kinesthetic learning style as much as (58%), class 7.5 is dominated by an Auditory learning style as much as (39%), class 7.6 is dominated by a Kinesthetic learning style as much as ( 58%), class 7.7 is dominated by the Auditorial learning style (35%). This research uses a qualitative approach with observation and interview methods adapted to the problem topic being discussed, namely Analysis of the VAK (Visual, Auditory, Kinesthetic) Learning Style Instrument for Students at MTsN 4 West Pasaman.